NITROGEN CONTENT OF TOPSOIL IN LOWLAND TROPICAL FOREST IN EAST KALIMANTAN (INDONESIA), BEFORE AND AFTER CLEAR-CUTTING AND BURNING - RlSWAN, SOEDARSONO (Research Center for Biology, 1984)
In order to study the changes in nitrogen content of forest soils after clearcutting and burning over a period of time, two plots of 0.5 ha in the primary mixed dipterocarp and kerangas forests were established and clear-cut. Thereafter, all felled vegetation in one plot of each forest type was burnt, while in the other plot the vegetation was removed from the plot without burning. Soil samples were collected along the transect line 1 x 100 m in each of plots at intervals of 20 m.The preliminary results of the data collected over 6 and 12 weeks after felling with or without burning showed a decline of total N and organic C contents of topsoil and an increase in soil pH.